IDENTIFICATION OF MIRNAS IN THEOBROMA CACAO L. THAT RESPOND TO PHYTOPHTHORA PALMIVORA FOR DEVELOPING BLACK POD DISEASE RESISTANT CACAO VARIETIES - Ulfa Ningsih, Devi
The decline in cocoa (Theobroma cacao L.) productivity in Indonesia due to black pod disease (BPD) has significantly impacted the Indonesian economy. The conventional strategy to control BPD caused by Phytophthora palmivora is using resistant varieties. Plant resistance can naturally be induced through the regulation of the expression of resistance genes as a manifestation of miRNA suppression that induces RNA interference. This study aims to identify T. cacao miRNAs that are significantly upregulated under P. palmivora attack and target T. cacao resistance genes themselves. miRNA silencing is predicted to increase the expression of resistance genes and make T. cacao resistant to P. palmivora. In this study, samples of resistant and susceptible varieties of T. cacao infected with P. palmivora were collected from the plantation of the Indonesian Coffee and Cocoa Research Institute, Jember, East Java, each with two replicates. small RNA was extracted using a mirPremier miRNA kit (Sigma Aldrich, Germany). Purity was obtained with an A260/280 ratio in the range of 1.8 - 2 and a concentration of 37.9 - 81.0 ng/?l from miRNA extraction. The miRNA isolates were sequenced on the Ilumina Novaseq 6000 platform (Novogen, Singapore). The miRNA sequencing results generated raw reads of 9 - 12 million reads. Raw reads were cleaned from adapters and filtered at a length of 18 - 28 bp using the Trimmomatic program, resulting in 2 - 10 million clean reads. The clean reads were then mapped to the T. cacao genome and quantified using the R subread package. From this study, 54 known miRNAs and 67 novel miRNAs were successfully quantified, 17 of which experienced differential expression. Nine up-regulated miRNAs were grouped to target plant defense response systems and pathogen resistance; photosynthesis, protein ubiquitination, DNA damage checkpoint signaling and DNA repair. Meanwhile, the eight miRNAs that were expressed down were grouped to target disease-resistant genes, receptor protein kinases, cell wall components, protein ubiquitination, seed growth, and vascular tissue structure. The miRNA candidates from this study are expected to be used in gene repression applications related to T. cacao resistance to P. palmivora through molecular technology approaches.